Considering Best Practices in Technical Ear Training - Wellington Gordon (Journal of the Association for Technology in Music Instruction, 2021)
Technical Ear Training (TET) is a new approach to preparing audio students for the professional environment. Systematic training develops the listening skills of student engineers and advances them as sensitive listeners. However, the current educational landscape lacks a nationally recognized curriculum that addresses specific characteristics of technical ear training. These characteristics include frequency identification (both boosts and cuts), gain, phase shift, delays, reverb times, and dynamics parameters. Targeted ear training methods can help students refine their technical listening skills and gain an increased technical vocabulary. This paper investigates multiple approaches to technical ear training, including data from an actual class using some of the methods presented in the paper; and it argues for a multi-faceted approach to ear training using new training software, analytical exercises, and headphone/speaker standards. The teaching model I applied in my professional practice offered a one-semester TET program that included frequency boosts and cuts identification with both pink noise and music. Results of the in-class assessments, online quizzes, and exams indicate an improvement with identifying frequency boosts and cuts in both music and pink noise. These data indicate that students are ready for new listening challenges, and that +10dB boost and -10dB cuts of pink noise can be removed by mid semester.
Keywords: Audio Training; Aural Skills; Critical Listening; Frequency Identification; Technical Ear Training